Independent and joint effects of sleep duration and sleep quality on suboptimal self-rated health in medical students: A cross-sectional study - Ding, Pan; Li, Jinyong; Chen, Huajian; Zhong, Chongzhou; Ye, Xiaoli; Shi, Hongying (Frontiers in Public Health, 2022)
Objective: This study aims to explore the independent and joint effects of sleep duration and sleep quality on suboptimal self-rated health (SRH) in medical students. Methods: Cross-sectional study. Proportional stratified cluster sampling was used to randomly recruit students from various medical specialties at a medical university in eastern China. Our questionnaire mainly included information on basic demographic characteristics, SRH, sleep behavior, and biorhythms. The independent and joint effects of sleep duration and sleep quality on suboptimal SRH were assessed by logistic regression after controlling for potential confounders. Results: Of 1524 medical students (mean age=19.9 years, SD=1.2 years; 59.1% female), 652 (42.8%) had suboptimal SRH. Most medical students (51.5%) slept for 7h/night, followed by ≥8h (29.1%) and ≤6h (19.4%). After adjusting for basic demographic characteristics and biorhythm information, compared with those who slept for ≥8h/night, the adjusted ORs (95%CI) for those who slept 7h and ≤6h/night were 1.36 (1.03, 1.81) and 2.28 (1.60, 3.26), respectively (P <0.001 for trend); compared with those who had good sleep quality, the adjusted ORs (95%CI) for those who had fair and poor sleep quality were 4.12 (3.11, 5.45) and 11.60 (6.57, 20.46), respectively (P <0.001 for trend). Further, compared with those who slept for ≥8h/night and good sleep quality, those who slept ≤6h and poor sleep quality had the highest odds of suboptimal SRH (OR 24.25, 95%CI 8.73, 67.34). Conclusions: Insufficient sleep and poor sleep quality were independently and jointly associated with higher odds of suboptimal SRH among medical students.